Costs of formal and informal care in the last year of life for patients in receipt of specialist palliative care. (April 2017) - Brick, Aoife; Smith, Samantha; Normand, Charles; O'Hara, Sinéad; Droog, Elsa; Tyrrell, Ella; Cunningham, Nathan; Johnston, Bridget
Background: Economic evaluation of palliative care has been slow to develop and the evidence base remains small. Aim: This article estimates formal and informal care costs in the last year of life for a sample of patients who received specialist palliative care in three different areas in Ireland. Design: Formal care costs are calculated for community, specialist palliative care, acute hospital and other services. Where possible, a bottom-up approach is used, multiplying service utilisation by unit cost. Informal care is valued at the replacement cost of care. Setting/participants: Data on utilisation were collected during 215 'after death' telephone interviews with a person centrally involved in the care in the last year of life of decedents who received specialist palliative care in three areas in Ireland with varying levels of specialist palliative care. Results: Mean total formal and informal costs in the last year of life do not vary significantly across the three areas. The components of formal costs, however, do vary across areas, particularly for hospital and specialist palliative care in the last 3 months of life. Conclusion: Costs in the last year of life for patients in receipt of specialist palliative care are considerable. Where inpatient hospice care is available, there are potential savings in hospital costs to offset specialist palliative care inpatient costs. Informal care accounts for a high proportion of costs during the last year of life in each area, underlining the important role of informal caregivers in palliative care.